Y = -1/2x - 1
Tell me if you need explanation
Answer:
walang keef fuzzy gasification
Answer:15 2/5
Step-by-step explanation:
23 - 7 = 16
16 - 3/5 → 15 5/5 - 3/5 = 15 2/5
Answer:
0.3 feet
Step-by-step explanation:
2.75(0.8)^x
in which x is the number of bounces after the firts bouce
bouce 12 would mean x=11
2.75(0.8)^11 = 0.2
Answer:
Given the function: y=f(x) = 3x+2
when x=-2 at the beginning of the interval [-2, 5],
then;
y = 3x+2 begins at
y= 3(-2)+2 = -6+2= -4.
and
when x=5 at the end of the interval [-2, 5],
y = 3x+2 ends up at
y= 3(5)+2 = 15+2= 17.
So,
y has changed -4 to 17, which is a change of 17-(-4)= 17+4 = 21
and x has changed from -2 to 5, which is a change of 5-(-2)=5+2=7
So, the average rate of change of y with respect to x over the interval
[-2, 5] is given by ;
=
Therefore, the average rate of change y with respect to x over the interval is, 3
Step-by-step explanation: